On measure preserving self-homeomorphisms of path spaces of simple stationary Bratteli diagrams - Lavrenyuk, Yaroslav (Київський національний університет імені Тараса Шевченка, 2018)
Borel measures which are invariant under the tail equivalence relation on path spaces of Bratteli diagrams are considered. We study the following problem: Let Bratteli diagram is fixed. Do every selfhomeomorphisms that preserve such a measure can be approximated by homeomorphisms which are “close to finitary” homeomorphisms? We found some conditions on diagrams for which it is true.Key words: Borel measure, path space, Bratteli diagram, homeomorphism group. Pages of the article in the issue: 30-35Language of the article: English

Borel measures which are invariant under the tail equivalence relation on path spaces of Bratteli diagrams are considered. We study the following problem: Let Bratteli diagram is fixed. Do every selfhomeomorphisms that preserve such a measure can be approximated by homeomorphisms which are “close to finitary” homeomorphisms? We found some conditions on diagrams for which it is true.Key words: Borel measure, path space, Bratteli diagram, homeomorphism group.Pages of the article in the issue: 30 - 35Language of the article: English
On measure preserving self-homeomorphisms of path spaces of simple stationary Bratteli diagrams